KAJIAN TEKNIS PENGGUNAAN UJI PDA (Pile Driven Analysis) PADA TIANG PONDASI - Yohanes Sibagariang; Valentana Tarigan; Budi Florianta Tarigan (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
Foundation work is an initial job that is usually done by all engineers in the construction of structures. Beginning with a soil investigation survey, then identification of the type and strength of the soil is carried out to determine the type of foundation that is suitable for the structure. In planning the foundation in building construction, it is necessary to investigate the soil parameters used in the calculation of the bearing capacity of the soil. The bearing capacity of the soil is very influential on the type and dimensions of the foundation, especially regarding the load carried by the foundation to be planned. A foundation is part of an engineering system that transmits the load supported by the foundation and its own weight to and into the soil and rock that lies beneath it. The resulting soil stresses except at the soil surface are in addition to the loads already present in the soil mass from its own weight. The borepile foundation made was 181 piles and the tested piles were 3 piles or 3/181 = 1.7%. The weight of the hammer used should be = ultimate bearing capacity *1% = 244.45 x 1% = 2.5 tons. While the weight of the hammer used in the field is 2.5 tons, meaning that it is sufficient. Hammer fall height = 1 – 1.2 m, so the hammer impact energy efficiency is 3.3-18%. For hammer impact energy efficiency for B-3 piles of 3.3% is considered inadequate.